The Concept of Sa‘Ādah According to Islamic, Western, and Greek Views - Mustaffa, Nurul Hidayawatie; Akhir, Noor Shakirah Mat
Sa‘ādah in Islam literally means happiness. In a broader sense, it also means a combination of peaceful and tranquil as well as being in luck. The concept of sa‘ādah has always been a topic of interest among the researchers local and foreign alike to better the livelihood of mankind, thus indicating the necessity of sa‘ādah in present times. Societies have a shallow understanding on the concept of sa‘ādah that it needs to be clearly discussed from Islamic, Western, and Greek perspectives. This research therefore aims to discuss the concept of sa‘ādah as per the views of the scholars selected from the Islamic, the western and the Greek disciplines. The discussion uses content analysis method by referring to the works and literatures penned by the above mentioned scholars pertaining to the concept of sa‘ādah. Thereafter, the data are analyzed using comparative method of which similarities and differences of the views on sa‘ādah are identified. The finding of the research show that there are a number of similarities among the views of the Islamic, the western and the Greek philosophers. However, this research also finds that the Islamic view of sa‘ādah is more comprehensive because it encompasses happiness in the present world as well as the hereafter.